Pengembangan Media Pembelajaran Berbasis Permainan Kartu Truth or Dare dalam Pembelajaran Tari di Sanggar Gandrung Dance Studio Kategori Usia 26-45 Tahun untuk Meningkatkan Kemampuan Menari - Erika Kharisma Damayanti; Kusumawardani, Dwi; Haerudin, Deden (Jurnal Pendidikan Tari, 2022)
The research method used is Research and Development using the 4D model proposed by S. Thiagarajan. there are 4 steps carried out 1) define; 2) design; 3) development. The data were collected by using observation data collection techniques, qualitative interviews, and quantitatively analyzed questionnaires. The results of the validation of the experts and the responses of the students stated that the learning media based on the Truth or Dare card game was very feasible in learning dance at Sanggar Gandrung Dance Studio, the learning outcomes reached 86% mastering the dance material provided and the students' dancing skills increased. In conclusion, this game media is a new innovation to be used in dance learning can help students learn dance knowledge and skills.